Complications of Internal jugular catheters in haemodialysis patients at a kidney care center in Nigeria - Hughes, Okafor Umezurike; Stella, Alade; Samuel, Edeh (Journal of Clinical Nephrology, 2019)
Internal jugular vein catheters (IJC) is recommended as the central venous access of choice in haemodialysis patients. However it is associated with complications of variable severity. Objectives: To study the complications associated with internal jugular vein catheters in haemodialysis patients in southern part of Nigeria. Methodology: The clinical details of patients who had IJC insertion at the kidney house, Hilton clinics Port Harcourt from 1st October 2011 to 30th September 2016 were documented. Complications from the IJC developed by the patients during the study period were also documented. The data obtained was analyzed using SPSS version 22. P value less than 0.05 was considered significant. Results: A total of 129 patients had 150 internal jugular catheter insertions. The mean age was 51.4±15.2 years with male to female ratio of 1.5:1. All the patients had chronic kidney disease; about 80% had tunneled IJC and 96.9% of the catheters were inserted in the right internal jugular vein. Immediate complications were recorded in 10% and late complications in 34.9% of the procedures. The immediate complications were kinking of guide wire (2%), arterial puncture (1.3%) and difficulty in locating the internal jugular vein (1.3%) or tunneling (1.3%). The late complications were infection (12.8%), poor blood flow (9.2%), bleeding (5.5%) and spontaneous removal of the catheter (5.5%). There was no statistical significant difference in both immediate and late complication with age and sex. The ultrasound examination at discharge had a sensitivity of 31% and specificity of 87% to detect future symptomatic lymphoceles. The positive predictive value was only 10%. The second ultrasound test had the best test variables to detect symptomatic lymphoceles with a sensitivity of 93% and a specificity of 87% and a predictive value of 28%. Conclusion: Internal jugular catheter is froth with immediate and late complications in haemodialysis patients.